The Effect of Motivation and Career Development on Nurses' Performance Through Nurses' Job Satisfaction at Pertamina Balikpapan Hospital - Lita Ripiani; Andini Nurwulandari; Hasanudin Hasanudin; Edi Sugiono (International Journal of Economics and Management Sciences, 2026)
This study aims to analyze the effects of work motivation and career development on nurses’ performance through job satisfaction among nurses at Pertamina Balikpapan Hospital. Nurses’ performance is a key determinant of service quality and patient safety because nurses interact most intensively with patients and ensure continuity of nursing care. However, prior studies on the relationships among motivation, career development, job satisfaction, and performance have reported mixed findings. Therefore, further examination is needed by incorporating job satisfaction as a mediating variable to explain the mechanism of influence more comprehensively. This research employed an explanatory design with a quantitative approach. Primary data were collected using a Likert-scale questionnaire distributed to 165 permanent nurses selected through purposive sampling from a population of 292 nurses. Data were analyzed using variance-based SEM with SmartPLS 4, including outer model evaluation (convergent and discriminant validity) and construct reliability, as well as inner model assessment through the coefficient of determination, effect size, and hypothesis testing using bootstrapping. The results indicate that work motivation has a positive and significant effect on job satisfaction, and career development also has a positive and significant effect on job satisfaction. Job satisfaction has a positive and significant effect on nurses’ performance. In addition, work motivation and career development have positive and significant direct effects on nurses’ performance. Indirect effect testing confirms that job satisfaction mediates the relationship between work motivation and nurses’ performance and also mediates the relationship between career development and nurses’ performance. These findings emphasize that hospitals should strengthen strategies to enhance motivation and career development in a targeted manner while ensuring key sources of job satisfaction so that nurses’ performance improves sustainably.